231k views
4 votes
If the difference of two numbers is even then so is their sum.

User Siler
by
5.9k points

1 Answer

6 votes

Answer and explanation:

Statement - If the difference of two numbers is even then so is their sum.

Let the two even numbers be '2m' and '2n' with m and n are integers.

The difference of two number is


2m-2n=2(m-n)

Now, The sum of the numbers is


2m+2n=2(m+n)

Let
m+n=k where k is an integer

Then,
2m+2n=2k which is also an even number as 2 is multiplied with it.

So, If the difference of two numbers is even then so is their sum.

For example -

Let two even number 2 and 4.

The difference is
4-2=2, 2 is even.

The sum is
4+2=6, 6 is even.

User QuokMoon
by
5.8k points